Structure and Dynamics of Heterogeneous Systems 2000
DOI: 10.1142/9789812793652_0013
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Pattern Propagation and Pulsed Laser Deposition

Abstract: In this article kinetic Monte Carlo simulations for molecular beam epitaxy (MBE) and pulsed laser depositon (PLD) are compared. It will be shown that an optimal pattern conservation during MBE is achieved for a specific ratio of diffusion to deposition rate. Further on pulsed laser deposition is presented as an alternative way to control layer by layer growth. First results concerning the island density in the submonolayer regime are shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…A comprehensive review can be found in [1] and the derivation of the reaction rate can be found in [2] with the mean-field approach. Particles can be injected into the system during time evolution [3][4][5][6][7], the injection of particles can be periodic in time [8,9]. For a very anisotropic surface the model is practically one dimensional [10,11].…”
mentioning
confidence: 99%
“…A comprehensive review can be found in [1] and the derivation of the reaction rate can be found in [2] with the mean-field approach. Particles can be injected into the system during time evolution [3][4][5][6][7], the injection of particles can be periodic in time [8,9]. For a very anisotropic surface the model is practically one dimensional [10,11].…”
mentioning
confidence: 99%